PERANCANGAN ALAT PENDETEKSI BANJIR DENGAN MEMANFAATKAN TINGGI MUKA AIR SKALA LABORATORIUM - Yoggi Hendra Safutra; Meilani Belladona; Tri Sefrus (Jurnal Teknologi, 2023)
Flood is one of the disasters that often hit in Indonesia which can occur every year. Flood is a natural disaster event that occurs when a water flow can no longer accommodate the volume of water. The flooding that occurred in Bengkulu City, especially in the prosperous swamp sub-district area, was caused by the high activity of the Bengkulu watershed due to coal mining upstream of the Bengkulu River Basin which had been carried out for a long time. The problem in this research is how to design a flood detector using laboratory scale water level. The purpose of the research to be carried out is to design a simple laboratory-scale flood detection mitigation tool that is useful for knowing the amount of water level rise in the Bangkahulu estuary river when a flood will occur. The method used in this study is the collection of primary data and secondary data on the Bangkahulu estuary river which will be scaled to obtain the results of making tools. The results of this study found that the normal water level at the research location was 3m, the height before the flood was 5.9 m, the height at the time of the flood was 8.44 m. A flood detection device has been tested, on a normal water level the device sounds with a time of 1 minute 46 seconds, discharge 0.18 liters/second, the water level alerts the tool sounds with a time of 1 minute 42 seconds, water discharge 0.18 liters/second and the water level is dangerous tool sound with a time of 1 minute 24 seconds water discharge 0.19 liters / second. This laboratory-scale flood detection tool can be a means of educating the community to minimize the impact of a flood disaster that can be understood by the community.